2009
DOI: 10.1143/jjap.48.071002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Controlled Growth Dynamics on the Microstructure of Nonpolar a-Plane GaN Revealed by X-ray Diffraction

Abstract: This paper reports the effect of controlled growth dynamics, as monitored by in situ optical reflectance, on the microstructure of nonpolar aplane GaN films grown on r -plane sapphire. The mosaic microstructure of a-plane GaN and its anisotropy are evaluated by X-ray rocking curve (XRC) measurements. By inserting a pronounced islanding stage followed by an enhanced lateral growth, pit-free a-plane GaN has been achieved showing an XRC linewidth of 0:18 and 0:3 for on-and off-axes planes, respectively, with only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 24 publications
0
44
0
Order By: Relevance
“…6. The measured values for the (3030) plane in the WH plots are located at much lower positions than the expected values from extrapolated lines for the other planes because the (3030) diffraction is not influenced by the existence of BSFs [6,28]. The figure clearly shows that the y-intercept (y 0 ) of the control sample (AG1, which lacks a SiN x interlayer) is higher than the yintercepts of the other samples (with different SiN x interlayers).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…6. The measured values for the (3030) plane in the WH plots are located at much lower positions than the expected values from extrapolated lines for the other planes because the (3030) diffraction is not influenced by the existence of BSFs [6,28]. The figure clearly shows that the y-intercept (y 0 ) of the control sample (AG1, which lacks a SiN x interlayer) is higher than the yintercepts of the other samples (with different SiN x interlayers).…”
Section: Resultsmentioning
confidence: 70%
“…For non-polar GaN, WH analysis is a useful tool for studying the mechanism governing anisotropic broadening in the XRD ω-scan of non-polar GaN films [11,28]. For example, McLaurin et al demonstrated that, when BSFs served as boundaries between incoherently scattering domains, these BSFs were responsible for ω-scan width anisotropy in m-plane GaN films [11].…”
Section: Resultsmentioning
confidence: 99%
“…5) and offaxis (Fig. 6) 0.2691, respectively, which are among the lowest values reported for a-plane GaN on r-plane sapphire without lateral epitaxial overgrown (LEO) process [15,18].…”
Section: Resultsmentioning
confidence: 78%
“…In the first step, a relatively high V/III ratio (1500) and reactor pressure (300 mbar) were applied for 10 min, in order to enable the GaN growth to start from a three-dimensional (3D) mode. Subsequently, the V/III molar ratio and reactor pressure were reduced to 200 and 100 mbar, respectively, which resulted in a fully coalesced surface [15]. A high-resolution X-ray diffractometer (Rigaku-Smartlab) was employed to evaluate the crystalline quality and anisotropy of the samples, delivering a CuKa1 line of wavelength l¼0.1541 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, there are some problems with these non-polar and semipolar GaN films, including a high threading dislocation (TD) density ( $10 9 cm À 2 ), intrinsic basal plane stacking faults (SFs) (density $ 10 5 cm À 2 ) and usually rough surface morphology. These problems can be improved using a variety of buffer layers, such as low temperature (LT) GaN or AlN, epitaxial lateral overgrowth and selective area growth (SAG) techniques [10][11][12][13]. Especially, SAG is a promising candidate technique to reduce TD and stacking faults densities and to control facets of 3D GaN structures easily that was successfully applied to c-plane pyramidal and microrings GaN structures [14][15] as well as to a-plane GaN [16].…”
Section: Introductionmentioning
confidence: 99%